2014
DOI: 10.1111/jgh.12600
|View full text |Cite
|
Sign up to set email alerts
|

Murine genetic deficiency of neuronal nitric oxide synthase (nNOS‐/‐) and interstitial cells of Cajal (W/Wv): Implications for achalasia?

Abstract: The reduction of ICC-IM and nNOS can cause dysfunction of the LES and esophageal peristalsis, whereas VIP reduction seems to have no effect. ICC-IM and nNOS deficiency might be independent relevant causes of esophageal dysfunction similar to that seen in human achalasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
(58 reference statements)
2
19
0
Order By: Relevance
“…In fact, in vitro incubation of the esophagus body with L-NG-Nitroarginine; NG-nitro-L-Arginine (nonspecific nitric oxide synthase inhibitor) increases the EFS-induced esophageal contractile responses (Lecea et al, 2011). Previous studies showed that neuronal NO synthase gene-deficient mice display uncoordinated and higher esophagus contractions compared with wild mice (Müller et al, 2014). In this study, neurogenic contractions were greater in esophagi from PHZ compared with control mice, suggesting increased nerve-evoked acetylcholine release in the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in vitro incubation of the esophagus body with L-NG-Nitroarginine; NG-nitro-L-Arginine (nonspecific nitric oxide synthase inhibitor) increases the EFS-induced esophageal contractile responses (Lecea et al, 2011). Previous studies showed that neuronal NO synthase gene-deficient mice display uncoordinated and higher esophagus contractions compared with wild mice (Müller et al, 2014). In this study, neurogenic contractions were greater in esophagi from PHZ compared with control mice, suggesting increased nerve-evoked acetylcholine release in the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that, like other cells, the number of ICCs is controlled by several factors that regulate proliferation and death and that ICCs continuously undergo apoptosis in the GI tract of healthy individuals [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Because neurons produce Stem Cell Factor (SCF), which activates the c-kit receptor and stimulates the proliferation, survival…”
Section: Resultsmentioning
confidence: 99%
“…Studies in mice have suggested that intramuscular ICCs may play a critical role in NO-dependent neurotransmission in the GI tract and the reduction of both have been implicated as cause of dysfunction of the lower esophageal sphincter and esophageal peristalsis in nNOS -/-and ICC -/-mice [19,20]. Decreased nitrergic innervation and loss of ICCs have been observed in idiopathic achalasia and those factors, in conjunction, have been considered to be implicated in such pathological process [21,22].…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…The interstitial cells of Cajal (ICCs) are the pacemaker cells of GI movement [15,16]. Therefore, loss of ICCs is strongly associated with several human GI motility disorders [17][18][19][20]. However, there are few reports of the efficacy of Rikkunshito on ICCs in murine small intestine.…”
Section: Introductionmentioning
confidence: 99%